2021
DOI: 10.1002/er.6907
|View full text |Cite
|
Sign up to set email alerts
|

Global research direction on Pt and Pt based electro‐catalysts for fuel cells application between 1990 and 2019: A bibliometric analysis

Abstract: Summary Platinum catalysts for use in fuel cells have gained much attention because of their unique properties such as high catalytic activity and durability. They have enabled a number of different electro‐catalysts for diverse applications. Nanomaterials based platinum (Pt) electro‐catalysts for fuel cell applications have been largely explored and actively utilised to meet those alternate energy needs. This bibliometric analysis examines developments from 1990 to 2019 in the area of Pt electro‐catalysts for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…Analysis of the country collaboration map revealed a significant number of publications resulting from collaborative research between other regions of the world, which agrees with the findings of Ojemaye et al [50]. Furthermore, it is encouraging that most publications from countries and journal sources receive more attention regarding the number of citations and referrals.…”
Section: Summary Of the Findingssupporting
confidence: 87%
See 1 more Smart Citation
“…Analysis of the country collaboration map revealed a significant number of publications resulting from collaborative research between other regions of the world, which agrees with the findings of Ojemaye et al [50]. Furthermore, it is encouraging that most publications from countries and journal sources receive more attention regarding the number of citations and referrals.…”
Section: Summary Of the Findingssupporting
confidence: 87%
“…This reason may not be distant from the reality that most advanced industries, institutions, research laboratories, and leading research centers in the world are found in developed countries [50,51]. Other contributing factors may include research grant opportunities, research and development (R&D) policies, technical progress factors, exchange program opportunities, and availability of state-of-the-art research facilities and environments in developed countries [50,51]…”
Section: Contributing Countriesmentioning
confidence: 99%
“…As one of the most promising energyconversion devices, proton-exchangemembrane fuel cells (PEMFCs) have been attracting much attention for many years. [1][2][3] It is known that the sluggish cathodic kinetics of the oxygen reduction reaction (ORR) greatly limits the conversion efficiency of PEMFCs. [4,5] To date, Pt (or Pt-based alloys) nanoparticles (NPs) loaded on a carbon support are still the most promising ORR catalysts due to their intrinsically high activity.…”
Section: Introductionmentioning
confidence: 99%
“…The fuel cell is deemed as an ultimate solution to solve the environment and energy crises due to its many advantages, such as high reliability and efficiency, no pollution and noise, and rapid response to load change 1 . Among various fuel cells (FCs), the low‐temperature proton exchange membrane FC (LT‐PEMFC) with a working temperature among 60°C~80°C is one of the most compatible choices in a natural environment 2 .…”
Section: Introductionmentioning
confidence: 99%